2012
DOI: 10.1002/ar.22617
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Immunohistochemical Features of the Vomeronasal System in Dogs

Abstract: Each of the structures integrating the sense of smell in mammals has a different degree of development, even in the so-called macrosmatic animals, according to the capacity of the olfactory system to detect thousands of different chemical signals. Such morphological diversity implies analogous physiological variation. The study of the accessory olfactory system, also known as the vomeronasal system, is a useful way to analyze the heterogeneity of the sense of smell. Macrodissection and microdissection methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
89
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(108 citation statements)
references
References 57 publications
14
89
0
5
Order By: Relevance
“…Although numerous studies of the canine nasal mucosa have been published (Lauruschkus, 1942; Müller, 1955; Neuhaus, 1955; Adams and Hotchkiss, 1983; Kavoi et al, 2010), we are unaware of any previous systematic search for these four or five OSbS in the dog. The findings reported above, together with our previous observation that the canine vomeronasal system binds anti-G αi2 but not anti-G αo antibodies (Salazar et al, 2013), show that the dog has only the main and vomeronasal subsystems, and that the latter is in all probability entirely VR1-based.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Although numerous studies of the canine nasal mucosa have been published (Lauruschkus, 1942; Müller, 1955; Neuhaus, 1955; Adams and Hotchkiss, 1983; Kavoi et al, 2010), we are unaware of any previous systematic search for these four or five OSbS in the dog. The findings reported above, together with our previous observation that the canine vomeronasal system binds anti-G αi2 but not anti-G αo antibodies (Salazar et al, 2013), show that the dog has only the main and vomeronasal subsystems, and that the latter is in all probability entirely VR1-based.…”
Section: Discussionsupporting
confidence: 67%
“…Histologically, the VNsE is composed of basal cells, receptor neurons and supporting cells, while the anterior part of the VNO duct features stratified squamous epithelium and the posterior part simple columnar epithelium (Figure 6 and Figure S6). The immunohistochemical features of the VNsE have recently been reported elsewhere (Salazar et al, 2013) and are commented on below in the Discussion.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The VNO of brown bears contained VNE, NSE, vomeronasal glands, vomeronasal cartilage and vessels like that of Asiastic black bears (Befu, 2009); histological features of the brown bear VNE are largely similar to those of dog (Salazar et al 2013). Receptor cells expressing OMP, which is known as a neuronal marker of differentiated receptor neurons of the olfactory system (Weiler & Benali, 2005), possessed both cilia and microvilli in the brown bear VNO, although these cells in mammals generally only have microvilli (Miragall et al 1979;Taniguchi & Mikami, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The VNO of rodents, marsupials and monotremes possesses both V1Rs-G ai2 and V2Rs-G ao (Jia & Halpern, 1996;Shi & Zhang, 2007;Brykczynska et al 2013). On the other hand, the vomeronasal system exclusively expresses V1Rs-G ai2 and degenerates functional V2Rs in most carnivores, ungulates and platyrrhini primates (Takigami et al 2000(Takigami et al , 2004Shi & Zhang, 2007;Young & Trask, 2007;Young et al 2010;Salazar & S anchez-Quinteiro, 2011;Hohenbrink et al 2012;Salazar et al 2013;Brykczynska et al 2013;Dinka et al 2016), whereas that of scaled reptiles exclusively possesses V2Rs-G ao and degenerates functional V1Rs (Kondoh et al 2013;Brykczynska et al 2013). The present immunohistochemical findings showed that G ai2 , but not G ao , is expressed in dendritic knobs of the vomeronasal sensory cells in the bear where receptors were located, indicating that the vomeronasal system mainly expresses V1R-G ai2 in bears as it does in other carnivores.…”
Section: Discussionmentioning
confidence: 99%